Densidade de semeadura e consórcio de braquiária e estilosantes visando à formação de cobertura vegetal para a cultura da soja - Lima, Gislaine Piccolo de (2012)
The tillage efficiency is directly related to the management and choice of vegetation species prior to sowing the crop. In this context, this study examined the effect of brachiaria sowing densities (Brachiaria ruziziensis) (10; 15 and 20 kg ha-1), stylosanthes (Stylosanthes macrocephala and Stylosanthes capitata) (3; 4.5 e 6 kg ha-1) and consortium of these species (10 + 3; 15 + 4.5; 20 + 6 kg ha-1) as vegetation cover for soybean crop and seed quality. Under field conditions in the agricultural years 2009/2010 and 2010/2011 were demarcated 3.5 m x 4.5 m plots with 1 m border between them for seeding cover crops. The cover crops were sown in August 2009 and 2010, period in which the incidence of invasive plants, biomass productivity, coverage persistence and soil coverage percentage promoted by plants were evaluated. At 90 days after sowing, before fruiting, covers were mowed and arranged on each respective plot. The soybean sowing was performed in early December 2009 and 2010, 20 days after mowing the cover, with 0.45 m spacing, seven sowing lines and 14 seeds per meter. In the soybean crop was determined the emergence speed index, emergence speed, emergence percentage and plant height; incidence of invasive plants, productivity; in addition to the physiological and nutritional quality of seed. The experimental design cover plants cycle and soybean was completely randomized with 10 treatments and five repetitions; means were submitted to regression analysis. The experimental design for seed quality data was completely randomized in 3 x 4 factorial arrangement, five repetitions; means compared by the by Scott and Knott test at 5% probability. The incidence of invasive plants and the fresh weight of narrow-leaf weeds in the cover crops had proportional reduction to the increase of planting density, in addition, cover crops with higher seeding rate showed higher percentage of ground cover. It was observed higher nutritional quality of seeds when grown under intercropping at intermediate sowing density (15 + 4.5 kg ha-1). In general, the results indicate the possibility of using the species Brachiaria ruziziensis in single condition or consortium, as cover crop prior to soybean; however, more detailed studies should be performed considering the species with the possibility of being used via crop rotation in the tillage system, as well as under regional climate and soil conditions